Peningkatan Pengetahuan Ibu Hamil Tentang Pencegahan Pre-Eklampsia - winnellia fridina sandy rangkuti; Sudarto; Susito; Sarliana Zaini; Witri (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Preeclampsia is a syndrome characterized by increased blood pressure and proteinuria that appears in the second trimester of pregnancy. This preeclampsia will usually recover in the postnatal period. Preeclampsia can occur in antenatal, intranatal, and postnatal. The prevalence of preeclampsia in developed countries is 1.8% -18%. The purpose of this activity is The purpose of this activity is to provide education about preeclampsia. The method used in this activity is by conducting tests (pre-test and post-test), before and after counseling is carried out to assess the level of knowledge or understanding of pregnant women about preeclampsia as an indicator of the success of a health promotion program. The results of counseling show that there is an increase in knowledge or understanding of pregnant women about preeclampsia, from 32 to 93 percent. Based on the results of this assessment, it is hoped that pregnant women can better understand control and be aware of preeclampsia.